Dosimetric comparison of helical tomotherapy (HT) with intensity modulated radiotherapy (IMRT), threedimension conformal radiotherapy (3D-CRT) and conventional two-dimension radiotherapy (2D) for craniospinal axis irradiation (CSI) - Supawongwattana, Bongkot; Hoonghual, Thikhamporn; Chitapanarux, Imjai; Wanwilairat, Somsak; Traisathit, Patrinee (Biomedical Sciences and Clinical Medicine, 2015)
Objective Helical tomotherapy (HT) can provide a radiation beam for a longer treatment field without a matching junction. The goal of this study was to evaluate the feasibility and potential dosimetric benefit in HT when compared with intensity modulated radiotherapy (IMRT), three-dimension conformal radiotherapy (3D-CRT) and two-dimension radiotherapy (2D). Methods Twelve newly diagnosed central nervous system (CNS) tumors requiring craniospinal axis irradiation (CSI) were treated with HT. The same computed tomography (CT) image datasets were re-planned with IMRT, 3D-CRT and 2D. Target dosimetric comparisons were categorized into the brain, spine and tumor boost planning target volume (PTV), and performed by an analysis of homogeneity index (HI) and conformity index (CI). The percentage of prescription and integral dose to the spinal cord and whole body (ID), respectively, were compared as well. Results HT achieved the best dosimetric distribution for brain PTV with a mean HI of 44.51% (p<0.001) and CI of 0.984 (p<0.001). The result of tumor boost PTV was almost identical to that of brain PTV. Regarding the spinal portion, HT and IMRT revealed an equal HI, while the CI was highest in HT (p<0.001) and compatible with the lowest prescription dose of 122.22% to the spinal cord. The ID of HT was comparable to the 2D technique (p=0.272) and signifi cantly inferior to 3D-CRT (p=0.034), while IMRT planning showed the highest ID (p<0.05). The mean overall treatment time was 40 days. Grade 3-4 hematologic toxicity was the only adverse event that caused a treatment break. Conclusion HT was feasible with shorter overall treatment time, and it also gave an excellent dosimetric distribution. Regarding ID, HT was inferior to 3D-CRT. Longer follow-up is required to evaluate this concerning issue.